1974
DOI: 10.2172/4218018
|View full text |Cite
|
Sign up to set email alerts
|

Ecological behavior of plutonium and americium in a freshwater ecosystem. Phase II. Implications of differences in transuranic isotopic ratios

Abstract: O n lanuary 19, 1975, research and development programs of the U.S. Atomic Energy Commission (AEC) became part of the newly formed Energy Research and Development Administration (ERDA). In this report, since it refers to work done in 1974, most references are to AEC programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Thus, no specific element K d values could be calculated. and Emery and Garland (1974) found no evidence that radiation dose at these facilities were limiting the algal, plant, or animal communities present even though calculated maximum dose rates reached 1 R per week and maximum gross beta levels reach 10 4 pCi/L in the water.…”
Section: Americiummentioning
confidence: 90%
See 2 more Smart Citations
“…Thus, no specific element K d values could be calculated. and Emery and Garland (1974) found no evidence that radiation dose at these facilities were limiting the algal, plant, or animal communities present even though calculated maximum dose rates reached 1 R per week and maximum gross beta levels reach 10 4 pCi/L in the water.…”
Section: Americiummentioning
confidence: 90%
“…Because the Columbia River bank sediments are not as fine-grained, a lower K d value of 500 mL/g was chosen, but the range was extended to values even larger than Livens et al (1994) found. and Emery and Garland (1974) studied pond sediments and pond water at U Pond on the Hanford Site in 200 West Area. On average, the pond sediments contained 53.9 pCi/g Am-241 and the overlying waters contained 1.1 pCi/L.…”
Section: Americiummentioning
confidence: 99%
See 1 more Smart Citation
“…The PFP FSAR (WHC-SD-CP-SAR-021), Table 9-44 gives the mass weighted isotopic concentrations for two categories of Pu material stored in the PFP--for material containing less than 10% Pu-240, and for material containing > 10% Pu-240. The bulk of the plutonium processed at PFP was weapons grade with an isotopic composition of approximately 93% Pu-239,6% Pu-240, and 0.6% Pu-241 (Emery and Garland 1974). In the late 1960's limited processing of fuel elements fiom power reactors occurred.…”
Section: G-hydrogen Generation Ratementioning
confidence: 99%
“…The bulk of the plutonium processed was weapons grade with an isotopic composition of approximately 93% Pu-239,6% Pu-240, and 0.6% Pu-241 (Emery and Garland, 1974). In the late 1960's, limited processing of fuel elements from power reactors occurred.…”
Section: Summary Of Sources Of Waste Sent To Tank 241-5361mentioning
confidence: 99%